Oil spill management using spatial technology - Shariah, Mohammed Abu; Assilzadeh, Hamid; Mansor, Shattri (2005)
Spatial technology is being used for oil spill research and development of activities that has been making important contributions to environment monitoring, modeling and management by examining the application of these technologies to the task of identifying vulnerable coastal locations before a spill happens and promptly perform removal actions and cleanup operation when an oil spill occurs. An oil spill contingency plan has been created for Straits of Malacca using SAR images to detect and map oil spill. Spatial technology has the ability to assessment and estimate the area and thickness of oil spill by creating hazard maps that leads to pollution region in the sea and by classifying the area to three categories; spill, low pollution and high pollution at Straits of Malacca. An Environmental sensitive index (ESI) map has been created as a quick reference for oil and chemical spill response and to support the contingency plan at a specific location. Prediction of oil spill trajectory model has been applied at Straits of Malacca to predict spill movement.